Long-term effects of physical training on cardiac function and structure in adolescent cross-country skiers. A 6.5-year longitudinal echocardiographic study - Tummavuori, M. (Studies in Sport, Physical Education and Health, 2004)
The purpose of this 6,5-year-follow-up study was to investigate the impact of training on the structure and function of the heart of young endurance athletes with the help of echocardiographic variables and maximal oxygen uptake (VO2max), which indicates the capacity of maximal cardiovascular function, This study also sought to determine at which age the structural and functional changes in the heart took place, the impact on cardiovascular function of short-time (6-7 months) training during three different training seasons, and the effect of body size and growth. The significance of the size of the heart at the baseline situation was examined by dividing the 16-year-old male cross-country skiers (n = 20) into two groups one comprising those with small hearts and the other comprising those with large hearts according to the end-diastolic diameter (EDD) of the left ventricle. EDD, septal wall thickness in diastole (SWTd) and posterior wall thickness in diastole (PWTd) of the left ventricle of the heart increased (7.8, 12.5 and 9.8 % respectively) significantly during the 6.5 years. EDD increased significantly during the first three years (age 16 - 19), while the walls remained unchanged, whereas during the last three years (age 19 - 22) EDD did not increase, but the walls thickened significantly. VO2max increased during the first three years and evened out thereafter. The annual echocardiographic changes and those of VO2max were small. There were no significant changes during the different training seasons. EDD, normalized with body surface area (BSA), did not change during the study. In the baseline situation the EDD of those with small hearts increased during the study more than the EDD of those with large hearts, but without reaching comparable values even at the end of the study. There were no differences in wall thickness between the groups. EDD increased more in the group where BSA had increased more. The skiers tended to have a larger EDD, and their SWTd and PWTd were thicker than those of control subjects of the same age. In conclusion it can be stated that genetic factors and growth had a great impact on the size of the heart of the skiers and control subjects, and that young cross-country skiers, thanks to endurance training, first experience dilatation of the left venhicle of the heart and then hvpertrophy of the walls.